Chroniques judiciaires du procès d’Oradour-sur-Glane et construction de la mémoire nationale (Bordeaux, 12 janvier 1953 – 13 février 1953) - Clarisse Blanc (Criminocorpus)
On January 12, 1953, the trial of the Oradour-sur-Glane massacre opened in front of the Military Tribunal of Bordeaux. On the bench of the accused, we find among the simple executors, the Malgré-nous alongside the Nazi soldiers. This trial is an obstacle to the construction of memory and the tensions between the Limousin and Alsatian populations are exacerbated by the holding of the trial. On the one hand, the national and Limousin newspapers advocate the recognition of the cruelty of the massacre as well as the need to judge Hitlerism and on the other hand, the Alsatian newspapers recall the constraint exerted on the Alsatian soldiers incorporated by force during the Occupation. This difference in this point of view revealed by the legal chronicles has repercussions on the construction of the national memory. The article is based on articles by court reporters dispatched to Bordeaux and attending the trial.